Coprotiella Venezuelensis, a New Record of Cleistothecia Genus of the Ascomycetes in the World - Delgado ívila, Adolfredo E.; Urdaneta García, Lilia M.; Piñeiro Chávez, Albino J. (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
A new record, Coprotiella venezuelensis was isolate on rhinoceros dung collected at south park Maracaibo zoo in Zulia State, Venezuela. The genus is compared with Coprotus and C. gongylospora having ascospores possessing De Bary bubbles